Exploring the Significant Factors Affecting the Social Crimes of Malaysian Students - Sam, Toong Hai; Isa, Khairunesa; Tong, Pang Kit; Palpanadan, Sarala Thulasi; Hong, Heng Chin; Bhutasang, Natchana (Journal of Ecohumanism, 2024)
This study aimed to explore factors hindering social crime among Malaysian students. 383 respondents, all students, were surveyed. Parental influence emerged as the most significant factor in dissuading students from social crime, according to mean score analysis. Correlation analysis revealed positive correlations between self-efficacy, peer pressure, mass media influence, parental influence, and Malaysian students' involvement in social crimes. The linear regression model, with a statistical significance below 0.05, indicated a strong fit for the data, suggesting its reliability. Mass media exerted the greatest influence on Malaysian students' involvement in social crimes, followed by peer pressure, self-efficacy, and parental influence. These findings offer insights for educational institutions, government officials, and policymakers to foster a culture of peace, justice, and strong institutions. Proactive measures can mitigate social conflicts and reduce crime rates, fostering individuals who contribute positively to society and support Sustainable Development Goal 16.